Strategi Komunikasi Bisnis Islami bagi Wirausahawan Startup melalui Media Sosial - Rif'ah, Sifwatir; Sa'idaturrohmah, Nur (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2025)
The implementation of Islamic business communication strategies through social media is an important key for startup entrepreneurs in building customer trust and loyalty. This study aims to analyze the Islamic business communication strategies implemented by startup entrepreneurs through social media and evaluate their effectiveness in improving business performance. This study uses a descriptive qualitative approach with a documentary method. The results show that the implementation of transparent, educational, and ethical Islamic-based communication can increase customer engagement, brand awareness, and consumer loyalty. This study is expected to provide insight for startup entrepreneurs in optimizing Islamic business communication strategies to achieve business sustainability based on Islamic values.